What Determines Households Willingness to Pay for Clean Water? - Muazzinah Muazzinah; M. Shabri Abd. Majid; Putri Bintusy Syathi (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2020)
This study aims to measure the households' Willingness to Pay (WTP) for clean water in Aceh Besar Regency and its determinants (i.e., income, education, family size, gender, and age). Of 16,164 households who have no access to clean water across seven sub-districts in the Aceh Besar region, 154 of them were selected as the sample of the study using a multi-stage random sampling technique. To measure the households' WTP for clean water and its determinants, this study uses the contingent valuation and multiple regression techniques. The study recorded that the average households' WTP for clean water was IDR444,123.38 per month. Based on multiple regression model, except for the variables of gender and age that have insignificant effect, the level of income, education, and family size were found to affect the households' WTP for clean water positively. These findings imply that to enhance households' WTP for clean water, the government should prioritize the rural-based economic, education, and family planning programs. Providing a more clean water distribution, followed by improving water and services quality at affordable prices would help the government to realize 100% access to clean water for all citizens in accordance with one of the SDGs' pillars.